The Experience Curve and the Market Size of Competitive Consumer Durable Markets - Joachim Kaldasch (Universitätsbibliothek, 2011)
An evolutionary model of the product life cycle is applied to derive the experience curve and the market size of (expensive) durable goods. The experience (learning) curve suggests that the real costs per unit decrease with an increasing cumulative output (Henderson's law). Based on the idea that in a competitive market firms are forced to pass cost advantages on to the price, the evolutionary model suggests that the mean price and also the mean costs are governed by an exponential decline with time. Simultaneously the mean price evolution satisfies Henderson's law. The market size is defined here by the number of active firms. The market size is shown to follow the total market revenue if the latter exhibits fast variations, else the size is nearly constant. A comparison with an empirical investigation confirms the model predictions.
Keywords: 330; experience curve; learning curve; market evolution; evolutionary economics; economic growth; product diffusion; Gompertz diffusion; product life cycle; durable goods; Lernprozess; Branchenentwicklung; Evolutionsökonomik; Wirtschaftswachstum; Innovationsdiffusion; Produktlebenszyklus; Konsumgut